2021
DOI: 10.1111/aogs.14121
|View full text |Cite
|
Sign up to set email alerts
|

Benefits and potential harms of human papillomavirus (HPV)‐based cervical cancer screening: A real‐world comparison of HPV testing versus cytology

Abstract: Introduction Human papillomavirus (HPV) testing as the primary cervical cancer screening method is implemented in several countries. We report data from the first round of a large Danish pilot implementation of HPV‐based screening. Our aim was to compare colposcopy referrals, detection of high‐grade cervical intraepithelial neoplasia (CIN) and cervical cancer, and positive predictive value (PPV) of colposcopy referral in HPV vs cytology‐based screening. Material and methods From May 2017 to October 2018, women… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

4
19
0
3

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 24 publications
(26 citation statements)
references
References 36 publications
4
19
0
3
Order By: Relevance
“…To our knowledge, the study by Zhao et al is the largest to date on the performance of HPV testing versus cytology for cervical cancer screening in a middleincome country. In line with findings from high-income settings [5,7,8], the authors found that HPV testing detected more cases of cervical intraepithelial neoplasia grade 2 or worse (CIN2+) than cytology-based screening, underlining the superior sensitivity of HPV testing. However, in contrast to results in high-income settings [7,8], the referral rate to immediate colposcopy was lower for HPV than cytology-based screening.…”
Section: Cervical Cancer Screening By Hpv Testingsupporting
confidence: 64%
See 3 more Smart Citations
“…To our knowledge, the study by Zhao et al is the largest to date on the performance of HPV testing versus cytology for cervical cancer screening in a middleincome country. In line with findings from high-income settings [5,7,8], the authors found that HPV testing detected more cases of cervical intraepithelial neoplasia grade 2 or worse (CIN2+) than cytology-based screening, underlining the superior sensitivity of HPV testing. However, in contrast to results in high-income settings [7,8], the referral rate to immediate colposcopy was lower for HPV than cytology-based screening.…”
Section: Cervical Cancer Screening By Hpv Testingsupporting
confidence: 64%
“…In line with findings from high-income settings [5,7,8], the authors found that HPV testing detected more cases of cervical intraepithelial neoplasia grade 2 or worse (CIN2+) than cytology-based screening, underlining the superior sensitivity of HPV testing. However, in contrast to results in high-income settings [7,8], the referral rate to immediate colposcopy was lower for HPV than cytology-based screening. As noted by the authors [10], this likely reflects that in the Chinese cytology-based screening program, all women with atypical squamous cells of undetermined significance or worse were referred directly to colposcopy, because not all laboratories could perform HPV triage testing for mild abnormalities, and compliance with repeat cytology could not be ensured [10].…”
Section: Cervical Cancer Screening By Hpv Testingsupporting
confidence: 64%
See 2 more Smart Citations
“…Since an increase of colposcopy referrals have been observed with the shift to HPV detection in cervical cancer screening [13,48], an introduction of all possibly carcinogenic HPV types into cervical cancer screening could potentially result in an additional increase of colposcopy referrals. The reason for this is that most HPV infections clear spontaneously without the need of any treatment.…”
Section: Discussionmentioning
confidence: 99%